Pengelolaan Pasar Kereng Pangi di Desa Hampalit Kecamatan Katingan Hilir: Management of Kereng Pangi Market in Hampalit Village, Katingan Hilir District - Karyadi, Karyadi; Mirdo, Mirdo (Pencerah Publik, 2017)
This study aims to describe and managerial analysis of Kereng Pangi Market Management conducted by the Office of Cooperatives, Small and Medium Enterprises, Trade and Industry, Katingan Regency. The method used in this research is the qualitative method. The technique of collecting data uses interviews, observation, and documentation. The data analysis technique in this study uses qualitative data analysis methods by reducing data, presenting data and verifying/drawing conclusions regarding the Management of Kereng Pangi Market in the Cooperative, Small and Medium Enterprises, Trade, and Industry, Katingan Regency. The results of the study prove that Kereng Pangi Market Management conducted by the Office of Cooperatives, Small and Medium Enterprises, Trade and Industry in Katingan Regency is still not optimal based on the indicators in this study, namely 1) Planning, 2) Organizing, 3) Direction and 4) Control.